Bioprospecting Through Cloning of Whole Natural Product Biosynthetic Gene Clusters - Lin, Zhenquan; Nielsen, Jens; Liu, Zihe (Frontiers in Bioengineering and Biotechnology, 2020)
Since the discovery of penicillin, natural products and their derivatives have been a valuable resource for drug discovery. With recent development of genome mining approaches in the post-genome era, a great number of natural product biosynthetic gene clusters (BGCs) have been identified and these can potentially be exploited for the discovery of novel natural products that can find application as pharmaceuticals. Since many BGCs are silent or do not express in native hosts under laboratory conditions, heterologous expression of BGCs in genetically tractable hosts becomes an attractive route to activate these BGCs to discover the corresponding products. Here, we highlight recent achievements in cloning and discovery of natural product biosynthetic pathways via intact BGC capturing, and discuss the prospects of high-throughput and multiplexed cloning of rational-designed gene clusters in the future.